Financial contagion in selected OIC countries-meta-analysis and new evidence - Hengchao, Zhang (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2020)
Since late 1990s, there has been an increasing number of studies exploring the phenomenon of financial contagion effects. Despite its significant implications, only limited number of studies have examined the contagion effects of the past financial crises on the stock markets of OIC countries. Among these studies, empirical findings on the evidences of the financial contagion effects in these OIC countries tend to be inconclusive. Having acknowledged the above-mentioned research gap, this thesis aims to explore the subject through two different angles, namely statistical analysis on past empirical literature and stock market data. At first, the classical meta-analysis is used to examine the evidence of financial contagion in the stock markets of OIC countries among the empirical literature over the last three decades. Having applied the Random-Effect Meta-Analysis approach, the Pooled Effect Size retrieved from 35 selected sampled studies reveal statistically significant financial contagion effect. This result indicates that the financial contagion effects in the OIC stock markets for the global financial crisis from 1990s and 2010s are statistically significant. The study then uses the meta-regression analysis to examine the sources of the varying results on past empirical financial contagion studies for the sampled countries. Through Weight Least Square (WLS) approach, the analysis finds that out of the 39 moderator variables, publication characters, data frequency, currency denomination, the varying crisis examined, the difference in financial contagion definition, and the empirical method used to test financial contagion are statistically significant. In other words, the difference in these moderator variables affect the statistical significance of the empirical findings for the sampled studies on financial contagion effects. This thesis then investigates the contagion effects of the Global Financial Crisis (GFC) and Euro Debt Crisis (EDC) on OIC stock markets based on the selected conventional as well as Islamic stock market indices. The Asymmetric Dynamic Conditional Correlation (A-DCC) GARCH model is applied in the study to take into account the asymmetric co-movements in conditional variance and correlations in the wake of negative shocks. In summary, our findings conclude that, except for GCC Islamic and conventional stock markets, the selected Islamic and conventional stock markets in OIC countries are all exempted from the financial contagion effects of GFC and EDC. These results imply that Islamic stock markets in OIC countries could be an effective diversification avenue for the portfolio investment to derive better returns, particularly during the global financial downturns. In addition, the intra-OIC portfolios investments may not be an effective diversification strategy for the risk mitigation during the financial turmoil. Finally, the short-term stabilization policies could be the effective stabilization policies for the OIC countries to mitigate the intra-OIC transmission of shocks during the global economic turbulence.